Molecular detection of tick-borne pathogens in infected dogs associated with Rhipicephalus sanguineus tick infestation in Thailand - Juasook, Amornrat (Vet World, 2021)
BACKGROUND AND AIM: Tick-borne pathogens (TBPs) are of great concern having the potential to threaten canine health. Dogs infected with Ehrlichia canis, Anaplasma platys, Babesia canis, and Hepatozoon canis are commonly found in Thailand; Rhipicephalus sanguineus tick is the most common vector of diseases. This study aimed to determine the prevalence of common TBPs in dogs and their ticks in Thailand using polymerase chain reaction (PCR) and DNA sequencing methods. MATERIALS AND METHODS: Forty-four blood samples were positively diagnosed with TBPs infection by microscopy. Samples were from animal hospitals in Maha Sarakham, Amnat Charoen, Nakhon Ratchasima, and Bangkok, Thailand, during January-June 2020. Five to six ticks were also taken from infected dogs, and then, both blood and tick were analyzed using PCR and DNA sequencing. RESULTS: PCR results showed that R. sanguineus was the only tick species detected in this study. The appearance of single infection with E. canis was the most common infection found in dogs and ticks (64% and 82%, respectively). Correlation of pathogen infection in hosts and their vector was performed by similarity detection of pathogens between blood and tick samples based on PCR analysis in 29 samples (66%) but there was no significant differentiation. CONCLUSION: E. canis appears as the most common canine tick-borne pathogen in Thailand, which was detected in both healthy and sick dogs as well as in R. sanguineus. The findings show the relationships among host dogs, pathogens, and ticks. Veterinarians should be proactive in educating pet owners about the risks associated with ticks and their important pathogens and plan effective control strategies.